NON-NUTRITIVE SUCKING HABITâ€“ THUMB SUCKING - Toseska-Spasova, Natasa; Dzipunova, Biljana; Tosheska-Trajkovska, Katerina; Spasov, Zoran; Karafilovska, Renata; Ivanov, Jelena; Jankulovska, Marija Jankulovska; Stavreva, Natasha (Journal of Morphological Sciences, 2019)
Oral habits is any repetitive behaviour that utilizes the oral cavity. Oral habits are learned patterns of muscular contractions.When habit cause defect in orofacial structure it is termed as pernicious oral habit. Oral habits in infancy and early childhood can be considered normal. The presence of an oral habit in the 3 to 6 year old is an important finding in the clinical examination. An oral habit is no longer considered â€œnormalâ€ for children near the end of this age group, because it may produce harmful effects on the development of maxillofacial complex. The lecture gives valuable informations about causative factors, prevalence and development of sucking oral habits. Clinical features and effects on the dentofacial complex caused by thumb sucking are presented and commented in detail. The lecture focuses on the management and treatment modalities of thumb sucking. At the end more information about pacifier sucking are commented. The identification and assessment of an abnormal habits and its immediate and long term effect on the craniofacial complex and dentition should be made as early as possible to minimize the potential deleterious effect on dentofacial complex.   Key words : oral habits, thumb sucking treatment